Dr. Wandia Njoya in Conversation with Prof. Dr. Carlos Kölbl - Njoya, Wandia; Kölbl, Carlos (Cluster Conversations, 2023)
In this latest episode of the Cluster Conversations Cluster fellow Dr. Wandia Njoya talks with Prof. Dr. Carlos Kölbl about her research project in which she researches new ways of conceiving and engaging with experiences of education in Kenya and other comparable contexts.